Analisis Penempatan Tugas dan Fungsi Kerja Tenaga Kesehatan di UPTD Puskesmas Binjai Kota - Yolanda Fidorova; Alya Indana Zulfa; Anggi Fadillah Putri; Dinda Febriani; Uci Yulan Ningsih; Fitriani Pramita Gurning (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Health Human Resources in health services is a form of efforts to plan, train, and develop health workers to support the achievement of the highest degree of health. The availability of quality health human resources, distributed fairly and evenly can ensure the implementation of health development. Puskesmas became the first health service facility for the community with promotive and preventive efforts. The lack of manpower and the uneven distribution of health workers in puskesmas will affect the degree of public health. This study aims to see how the placement of duties and work functions of health workers in UPTD Puskesmas Binjai Kota based on aspects of procurement, development, and maintenance. The type of research used is qualitative research with a descriptive approach and literature studies, namely observation, in-depth interviews and documentation. The results of the study obtained that the UPTD Puskesmas Binjai Kota has an excessive number of health workers with task placements that are not in accordance with their expertise and the low capacity of their human resources for computer operations. Therefore, proper planning and self-awareness of each individual are needed so that services at puskesmas can run optimally.